"We Take Care of Patients, but We Don't Advocate for Them": Advance Care Planning in Prison or Jail. Issue 12 (9th October 2018) - Ekaireb, Rachel; Ahalt, Cyrus; Sudore, Rebecca; Metzger, Lia; Williams, Brie
Abstract : Objectives: To investigate correctional healthcare providers' knowledge of and experience with advance care planning (ACP), their perspectives on barriers to ACP in correctional settings, and how to overcome those barriers. Design: Qualitative. Setting: Four prisons in 2 states and 1 large city jail in a third state. Participants: Correctional healthcare providers (e.g., physicians, nurses, social workers; N=24). Results: Participants demonstrated low baseline ACP knowledge; 85% reported familiarity with ACP, but only 42% provided accurate definitions. Fundamental misconceptions included the belief that providers provided ACP without soliciting inmate input. Multiple ACP barriers were identified, many of which are unique to prison and jail facilities, including provider uncertainty about the legal validity of ACP documents in prison or jail, inmate mistrust of the correctional healthcare system, inmates' isolation from family and friends, and institutional policies that restrict use of ACP. Clinicians' suggestions for overcoming those barriers included ACP training for clinicians, creating psychosocial support opportunities for inmates, revising policies that limit ACP, and systematically integrating ACP into healthcare practice. Conclusion: Despite an increasing number of older and seriously ill individuals in prisons and jails, many correctional healthcare providers lack knowledge about ACP. In addition to ACP barriers found in the community, there are unique barriers to ACP in prisons and jails. Future research and policy innovation are needed to develop clinical training programs and identify ACP implementation strategies for use in correctional settings.J Am Geriatr Soc 66:2382–2388, 2018 .